Plant selection initiates alternative successional trajectories in the soil microbial community after disturbance. Issue 3 (21st May 2019) - Duhamel, Marie; Wan, Joe; Bogar, Laura M.; Segnitz, R. Max; Duncritts, Nora C.; Peay, Kabir G.
Abstract: Because interactions between plants and microbial organisms can influence species diversity and rates of nutrient cycling, how plants shape microbial communities is fundamental to understanding the structure of ecosystems. Despite this, the spatial and temporal scales over which plants influence microbial communities is poorly understood, particularly whether past abiotic or biotic legacies strongly constrain microbial community development. We examined biogeochemical cycling and microbial community structure in a coastal landscape where historical patterns of vegetation transition after a large fire in 1995 are well known, allowing us to account for past abiotic and biotic conditions. We found that alternative states in microbial community structure and ecosystem processes emerged under different plant species, regardless of past conditions. Greenhouse studies further demonstrated that these differences arise from direct plant selection of microbes, with selection stronger in roots compared with soils, especially for bacteria. Correlation of microbial community structure with seedling growth rates was also stronger for fungi compared to bacteria. Despite these effects, minimal overlap between seedling and field microbial communities indicates that the effects of initial plant selection are not stable; rather, plant selection initiated alternative successional trajectories after the fire. Using data from a guild where we have abundant natural history information, ectomycorrhizal fungi, we show that greenhouse communities are dominated by ruderal taxa that are also common in the field after the fire and that these ruderal fungi strongly alter spatial patterns in plant–soil feedback, enabling invasion and transformation of soils previously occupied by heterospecific plants, thus potentially acting as keystone mutualists.